An IoT-enabled device for remotely monitoring and controlling solar photovoltaic systems - Srinivasan P.; Kannan K. (EAI Endorsed Transactions on Scalable Information Systems, 2024)
This article presents an Internet of Things (IOT) solution that focuses on managing and tracking the operation of a solar system and is intended for both home and commercial application. A MOSFET driver, a DC-DC SEPIC converter, a single-phase voltage source inverter with active clamping, and a DC-DC Landsman converter are all used by the system to condition electricity. This allows for real-time online contact with an internet server and includes measurements of the output voltage and current from the solar panel and battery to monitor DC load and AC load. The ESP32 Wi-Fi MOD and PIC microcontroller work together to seamlessly provide an online connection to the internet server. The outcomes of the experiments demonstrate how well voltage control works and how well IOT functions. Through a user-friendly GUI interface on the internet, users can effortlessly control the DC-DC converter and get real-time data on battery voltage, current, and state of charge by combining solar energy with the power source.